Integration of Empirical Methods for Accurate Water Saturation Calculation in Low Resistivity Reservoir - Citrowati, Sekar Ayu; Dedy Irawan; Pahala Dominicus Sinurat (Penerbitan Universitas Trisakti, 2024)
The Indonesian oil and gas industry faces significant challenges in exploring low-resistivity reservoirs, such as the Talang Akar Formation in South Sumatra, the Tanjung Formation in East Kalimantan, and the Gumai Formation in South Sumatra and West Java. These reservoirs often contain clay, clayey sand, and conductive minerals, which complicate geophysical log interpretation, leading to missed hydrocarbon potential. Common methods such as Archie’s Law are often used to calculate water saturation but tend to be inaccurate in formations with high conductivity due to clay content. The Simandoux method attempts to address this limitation by considering the conductivity of clay, but the assumption of homogeneous clay distribution often does not match actual conditions. This study proposes a modification to the Simandoux method by accounting for the non-linear behavior of clay conductivity and formation-specific parameters derived from core analysis. This approach integrates multi-parameter log data and advanced petrophysical models to address mineralogical heterogeneity and clay distribution. The results show that the modified Simandoux method provides more accurate water saturation estimates in low-resistivity zones. Validation with core and production data demonstrates the improved reliability of this model, supporting optimal field development and hydrocarbon exploration in Indonesia.